Decreased expression of insulin-degrading enzyme increases gluconeogenesis and glucose production in cultured hepatocytes administered with glucagon - González-Casimiro, Carlos M.; Cámara-Torres, Patricia; Merino, Beatriz; Astudillo, Alma M.; de la Fuente, Miguel A.; Ramírez, Cristina M.; Alonso, Andrés; Cózar-Castellano, Irene; Perdomo, Germán (Scientific reports, 2025)
Insulin-degrading enzyme (IDE) is a protein with proteolytic and non-proteolytic functions that regulates glucose homeostasis. In the fasted state, glucagon regulates glycemia through induction of hepatic gluconeogenesis. The rate of hepatic gluconeogenesis is elevated in subjects with type 2 diabetes (T2D) compared with healthy subjects. Interestingly, subjects with T2D show decreased expression of hepatic IDE. However, the role of IDE on the regulation of hepatic gluconeogenesis is completely unknow. We hypothesize that IDE deficiency alters glucagon signaling and thereby gluconeogenesis. To test this hypothesis, we used mouse liver tissues and cultured hepatocytes with total or partial IDE deficiency. The glucagon signaling pathway, expression of gluconeogenic genes, glucose production, and transcriptomic analysis were performed in control and IDE-KO hepatocytes. Total or partial loss of IDE in liver tissues or cultured mouse hepatocytes resulted in lower levels of the glucagon receptor (GCGR) and the cAMP-response element binding protein (CREB). However, glucagon stimulation increased the phosphorylation of CREB, despite lower levels of cAMP in IDE-deficient mouse hepatocytes. The activation of CREB was associated with an upregulation of the gluconeogenic genes Pck1 and G6pc (~ 200% and ~ 70% respectively) and higher glucose production in IDE-deficient mouse hepatocytes. Finally, genetic depletion of IDE in HepG2 hepatocytes led to upregulation of genes involved in cellular functions related to membranes, organelles and signaling receptors. These findings may be of relevance to better understand the regulation of hepatic gluconeogenesis and the use of IDE as a potential therapeutic target for the treatment of T2D.